A Comparative Study of Biomarker Levels for Iraqi Individuals’ Smokers and Non-Smokers Depending on the Duration of Smoking - Abbood, Shaymaa Saadi; Ibraheem, Aseel Khalil; Hashim, Heyam A; Challoob, Muntadher Hussein (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Smoking is a widespread public health challenge globally, impacting societal health and economy while elevating the risk of cardiovascular and peripheral vascular diseases. This study aims to examine hematological parameters (HB, PCV%, WBC, RBC, PLT, ESR), liver and kidney function, lipid profile, and electrolytes (K+, Na+, Ca++) in male smokers aged 20-55 from Baghdad City, subdivided by smoking duration (≥5 years and <5 years), compared to non-smoking controls. A total of sixty participants were recruited across three areas (Diyala Bridge, Mada'in, Talbieh), with each group comprising thirty individuals. Venipuncture was performed for blood sample collection. Results revealed statistically significant elevations in total WBC and RBC counts, hematocrit, hemoglobin, total cholesterol, and liver enzymes (GOT, GPT, ALP) among smokers compared to non-smokers (p<0.05 or p<0.001). Serum uric acid, urea, and creatinine levels were significantly higher in smokers (p<0.001), while triglyceride levels showed no significant difference (p>0.05) between groups. Smokers with longer duration (>5 years) exhibited higher HB, triglyceride, and Na+ levels compared to shorter-term smokers. Sensitivity analysis indicated Na+ as a potentially effective biomarker for smoking-related health impacts, complementing PCV% and urea sensitivity. The study underscores the association between smoking and oxidative stress, notably reflected in elevated GOT and GPT levels, suggesting implications for antioxidant therapies in managing smoking-induced oxidative damage. These findings contribute novel insights into biomarker responses influenced by smoking duration and advocate for targeted public health strategies and further research into antioxidant interventions to mitigate smoking-associated health risks effectively.